SPE Formation Damage Control Symposium 1996
DOI: 10.2118/31094-ms
|View full text |Cite
|
Sign up to set email alerts
|

Field Study of Guar Removal from Hydraulic Fractures

Abstract: To maximize well productivity, it is essential to maximize fracture cleanup. A field study in the Codell formation of Colorado was conducted to examine the effects of guar removal from hydraulic fractures on gas production.The conventional method of quantifying cleanup from a hydraulic fracture has been to report load water recovery; however, this value is affected by any formation water that might be produced. A more quantifiable approach to describing fracture cleanup has been performed in this study by dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…He concluded that in low permeability formations, Pc and relative permeability in invaded zones are significantly important on cleanup efficiency but in his work, the impact of FF volume on the conductivity of the fracture was not investigated. Pope et al (1996) presented a positive relationship between load recovery and gas production from field data. They explained that as FF is produced back to the surface from HF, an equivalent space in the fracture becomes available to the flow of the gas toward the well.…”
Section: Introduction and Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…He concluded that in low permeability formations, Pc and relative permeability in invaded zones are significantly important on cleanup efficiency but in his work, the impact of FF volume on the conductivity of the fracture was not investigated. Pope et al (1996) presented a positive relationship between load recovery and gas production from field data. They explained that as FF is produced back to the surface from HF, an equivalent space in the fracture becomes available to the flow of the gas toward the well.…”
Section: Introduction and Literature Reviewmentioning
confidence: 94%
“…There are several experimental, numerical and field studies investigating the impact of the cleanup efficiency of hydraulic fractures on gas production and FF flowback in unconventional tight/ultra-tight formations (e.g. Pope et al, 1996;Gdanski et al, 2005).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Understanding and modeling the recovery of gel filtercakes, whether permanently crosslinked with metals or reversibly crosslinked with boron, continues to be a subject of interest (Asadi et al 2008;Hutchins et al 2011). Field studies have indicated a positive correlation between gel recovery and gas productivity (Pope et al 1996). This has helped drive laboratory and numerical studies into areas that might improve gel recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Their correlation is extensively utilized in the oil and gas industry with an acceptable error. There have been several other research works on the development of theoretical models [20][21][22][23][24][25]. Gilbert (1954) was the first researcher to suggest the an empirical correlation by using 268 production data sets taken from an oil field in California, for choke sizes ranging from 6/64 to 18/64.…”
mentioning
confidence: 99%
“…• P wh : Upstream (wellhead) pressure, psi. Many researchers have developed Gilbert-type empirical correlations for the prediction of choke performance under critical conditions [25][26][27][28][29][30][31][32][33]. All empirical correlations have been developed using production data sets taken from some specific fields [34][35][36][37][38]; therefore, these empirical correlations are usually accurate within production parameter variation ranges from which they have been developed.…”
mentioning
confidence: 99%